A Low Power, Low Noise Amplifier for Recording Neural Signals - G. Deepika; K.S. Rao (Institute of Advanced Engineering and Science, 2017)
The design of a low power amplifier for recording EEG signals is presented. The low noise design techniques are used in this design to achieve low input referred noise that is near the theoretical limit of any amplifier using a differential pair as input stage. To record the neural spikes or local field potentials (LFP’s) the amplifier’s bandwidth can be adjusted. In order to reject common-mode and power supply noise differential input pair need to be included in the design. The amplifier achieved a gain of 53.7dB with a band width of 0.5Hz to1.1 kHz and input referred noise measured as 357 nVrms operated with a supply voltage of 1.0V. The total power consumed is around 3.19µW. When configured to record neural signals the gain measured is 54.3 dB for a bandwidth of 100 Hz and the input referred noise is 1.04µ Vrms. The amplifier was implemented in 180nm technology and simulated using Cadence Virtuoso.